Breaking News Websites’ Responses to Political Assassination in the United States and Poland - Burno-Kaliszuk, Karolina (Roczniki Nauk Społecznych, 2025)
The ways in which political assassinations are reported by the media can vary due to existing divisions in society, as well as factors such as the political prominence of the victim or the direct effect of the attack. In order to examine changes in such narratives, 703 articles on the assassination attempts on Donald Trump and Paweł Adamowicz from leading American and Polish news websites were analysed. The study established that the news media expose pre-existing political divisions and that the most important factor influencing the shape of the discourse is the global recognition of the victim.